Identifikasi Kepribadian Ideal Konselor Khas Budaya Indonesia : Kajian Nilai-Nilai Luhur Gusjigang Berdasarkan Perspektif Hermeneutika Gadamerian - Sunarti Sunarti; Bakhrudin All Habsy (Indonesian Journal of Learning Education and Counseling, 2018)
The study of Gusjigang's noble values is based on the importance of counselors to understand noble values and cultural significance in counseling practice. Gusjigang is a series of noble teachings of Sunan Kudus formulated in three main pillars of Gus is meaningful good, Ji which means skill in studying, and Gang meaningful trade. The research method used is qualitative approach with Gadamerian hermeneutical analysis type. The Gadamerian hermeneutic point of thought exists in a hermeneutic circle pattern. The circle consists of a pattern of up and down between parts and whole to understand the meaning in a text. The focus of this research is to describe the noble values in Gusjigang philosophy which then used to be an ideal personality characteristic of Indonesian cultural counselor.